A case of abdominal tuberculosis presenting as obstructive jaundice - Naik, Suresh; Kulkarni, Bahar; Shrotriya, Siddhant; Ghade, Kirankumar B. (International Journal of Research in Medical Sciences, 2024)
Extrapulmonary tuberculosis is notorious for its many manifestations, which can lead to delayed diagnosis and treatment. In particular, abdominal tuberculosis is easily overlooked because the incidence is low and because it can mimic common non-infectious abdominal syndromes. We describe here a 45-year-old female presenting with obstructive jaundice. In this patient, a pancreatic mass was found and tuberculosis was first diagnosed after a diagnostic laparoscopic. Tuberculosis should be included in the differential diagnosis of intra-abdominal mass lesions, especially in persons originating from regions where tuberculosis is endemic. Invasive procedures are often required to obtain adequate diagnostic samples.